miR-379 mediates insulin resistance and obesity through impaired angiogenesis and adipogenesis regulated by ER stress - Maryam Abdollahi; Mitsuo Kato; Linda Lanting; Ragadeepthi Tunduguru; Mei Wang; Yangmeng Wang; Patrick T. Fueger; Qiong Wang; Wendong Huang; Rama Natarajan (Elsevier, 2022)
We investigated the role of microRNA (miR-379) in the pathogenesis of obesity, adipose tissue dysfunction, and insulin resistance (IR). We used miR-379 knockout (miR-379KO) mice to test whether loss of miR-379 affects high-fat diet (HFD)-induced obesity and IR via dysregulation of key miR-379 targets in adipose tissue. Increases in body weight, hyperinsulinemia, and IR in wild-type (WT)-HFD mice were significantly attenuated in miR-379KO-HFD mice with some sex differences. Relative to control chow-fed mice, in WT-HFD mice, expression of miR-379 and C/EBP homologous protein (Chop) (pro-endoplasmic reticulum [ER] stress) and inflammation in perigonadal white adipose tissue (gWAT) were increased, whereas adipogenic genes and miR-379 target genes (Vegfb and Edem3) were decreased. These changes, as well as key parameters of brown adipose tissue dysfunction (including mitochondrial defects), were significantly attenuated in miR-379KO-HFD mice. WAT from obese human subjects with and without type 2 diabetes showed increased miR-379 and decreased miR-379 target genes. In cultured 3T3L1 pre-adipocytes, miR-379 inhibitors increased miR-379 targets and adipogenic genes. These data suggest that miR-379 plays an important role in HFD-induced obesity through increased adipose inflammation, mitochondrial dysfunction, and ER stress as well as impaired adipogenesis and angiogenesis. miR-379 inhibitors may be developed as novel therapies for obesity and associated complications.